729 "I Don't Feel Like I'm Learning How to Be A Doctor:" The Impact of Disruptions Due to Covid-19 On Professional Identity Formation in UK Medical Students. (12th October 2021) - Harvey, A; Brown, M E L; Byrne, M H V; Ashcroft, J; Wan, J C M; Alexander, L; Schindler, N; Brassett, C
Abstract: Introduction: Professional identity formation (PIF) is a priority of medical training. Covid-19 caused disruption to medical education. We ask how this disruption impacted PIF through the lens of the activities performed – or not performed – by medical students during the first wave of the covid-19 pandemic, and perceptions of conflicts between activities. Method: A pragmatic survey was distributed in spring 2020. Thematic analysis was performed of qualitative responses to two open questions. A social constructivist approach linked participants' comments to PIF theory. Results: We analysed 928 responses. Three themes surrounding students' activities during covid-19 and their impact on identity were constructed: Status and role as a future doctor Status and role as a student Status and role as a member of the wider community Conflict arose at the intersections between these themes. Students noted lack of clinical exposure was detrimental, implicitly recognising that aspects of PIF require the clinical environment. Participants were keen to volunteer but struggled with balancing academic work. Participants worried about risk to their households and the wider community and wanted their skills to add value in the clinical environment. Volunteers felt frustrated when they were unable to perform tasks aligning with their identity as a future doctor. An exception was participants who worked as interim FY1s, aligned with the role of an FY1. Conclusions: Medical students feel a duty to help during crises. Conflict arises when different aspects of their identity demand different actions. Care must be taken to nurture PIF during periods of disruption.